Study of the Immunological Status of Iraqi Vitiligo Patients - Baghdad Science Journal (مجلة بغداد للعلوم)
Vitiligo is an acquired idiopathic skin disorder characterized by depigmented macules due to loss of cutaneous melanocytes. A potential role of the immune dysfunction has been suggested in vitiligo, so to test this hypothesis, certain cytokines (IL-17A and TNF-?) and immunoglobulins (IgM, IgG, IgA and total IgE) were investigated in all participants. The study included: 60 patients with age range between (6-55) year; 30(11 males and 19 females) were untreated and 30(12 males and 18 females) were treated with Narrow Band Ultraviolet-B (NB-UVB) and 30 (14 males and 16 females) apparently healthy control. Serum was separated and cytokines (IL-17A and TNF-?) and total immunoglobulin E (IgE) were detected by using Enzyme Linked Immunosorbent Assay (ELISA); while immunoglobulins (IgM, IgG and IgA) were detected by using Single Radial Immunodiffusion (SRID) method. The results showed that the mean levels of serum IL-17A and TNF-? in both untreated and NB-UVB treated vitiligo patients were increased significantly (p ? 0.05) as compared with healthy control. The mean levels of serum IgG and IgA in untreated vitiligo patients showed non significant decreased (P